Semiotic Analysis of Teenagers' Struggles in TXT's Music Videos from "The Chaos Chapter: Fight or Escape" Album - Putri, Tiara Jas; Jufrizal, Jufrizal (English Language and Literature, 2024)
Due to the increasing cases of mental health in teenagers, TXT tries to represent the various problems and struggles faced by teenagers today in the music videos on one of their albums. This research was conducted to see the visual and verbal signs and denotative meanings, connotative meanings, and myths that represent the struggles of teenagers found in the TXT’s music videos from The Chaos Chapter: FIGHT OR ESCAPE album. This research analyzed scenes out of three music videos.  Semiotic theory by Barthes (1967) was used in this study with qualitative approach. Visual signs found include family issues, hallucinations, act impulsively, desire to be freedom and so on. While verbal signs found are, feeling of isolation, hallucinations, have feelings of sorrow, and identity crisis. Meanwhile, the denotative meanings found include family issues, thinking friends are everything, giving up easily and so on. On the other hand, the connotative meanings found are often running away from problems, like to do things that hurt themselves, confused about their own life. While the myths found are, teenagers often run away from home to find a sense of security and comfort that they don't find at home and think that suicide is not wrong.